A Research to The Solar Coronal Initial Magnetic Dynamics Prior a Launch of CME - Setiahadi, Bambang; Kamarudin, Farahana; Sujito, S; Wisodo, Hari (Universitas Muhammadiyah Surakarta, 2020)
Two dimensional magnetic-structures is developed and derived in the basic assumption line-tied condition in solar plasma. The type is two-dimensional half-circle magnetic arcade topology imbedded in photosphere dense plasma. The magnetic topology is assumed to be converted dynamically due to disturbance in magnetic fields and became a CME. Disturbance is derived from magneto-hydrostatic condition and perturbation is applied as first-order small deviation along the magnetic fields. Along the base of the magnetic arcade every disturbance is assumed to be zeroed by dense plasma and the magnetic fields of line is line-tied on photosphere. By inspecting snapshot data it is found that the derived structure is similar with solar coronal magnetic structure prior a launch of CME from coronagraph white light data.